Workplace resources to improve both employee well-being and performance: A systematic review and meta-analysis - Nielsen, Karina; Nielsen, Morten B.; Ogbonnaya, Chidiebere; Känsälä, Marja; Saari, Eveliina; Isaksson, Kerstin (Work and stress, 2017)
Organisations are becoming increasingly aware of the importance of employees in gaining and maintaining competitive advantage. The happy worker-productive worker thesis suggests that workers who experience high levels of well-being also perform well and vice versa; however, organisations need to know how to ensure such happy and productive workers. The present review and meta-analysis identifies workplace resources at the individual, the group, the leader, and the organisational levels that are related to both employee well-being and organisational performance. We examine which types of resources are most important in predicting both employee well-being and performance. We identified 84 quantitative studies published in print and online from 2003 to November 2015. Resources at either of the four levels were related to both employee well-being and performance. We found no significant differences in employee well-being and organisational performance between the four levels of workplace resources, suggesting that interventions may focus on any of these levels. Cross-sectional studies showed stronger relationships with well-being and performance than longitudinal studies. Studies using objective performance ratings provided weaker relationships between resources and performance than self-rated and leader/third-party-rated studies.